Multiplex surface-enhanced Raman scattering identification and quantification of urine metabolites in patient samples within 30 min - Kao, Ya-Chuan (2020)
Successful translation of laboratory-based surface-enhanced Raman scattering (SERS) platforms to clinical applications requires multiplex and ultratrace detection of small biomarker molecules from a complex biofluid. However, these biomarker molecules generally exhibit low Raman scattering cross sections and do not possess specific affinity to plasmonic nanoparticle surfaces, significantly increasing the challenge of detecting them at low concentrations. Herein, we demonstrate a "confine-and-capture" approach for multiplex detection of two families of urine metabolites correlated with miscarriage risks, 5β-pregnane-3α,20α-diol-3α-glucuronide and tetrahydrocortisone. To enhance SERS signals by 1012-fold, we use specific nanoscale surface chemistry for targeted metabolite capture from a complex urine matrix prior to confining them on a superhydrophobic SERS platform. We then apply chemometrics, including principal component analysis and partial least-squares regression, to convert molecular fingerprint information into quantifiable readouts. The whole screening procedure requires only 30 min, including urine pretreatment, sample drying on the SERS platform, SERS measurements, and chemometric analyses. These readouts correlate well with the pregnancy outcomes in a case-control study of 40 patients presenting threatened miscarriage symptoms.